Changes of Physicochemical and Microbiological Properties of Blended Sweet and Sour Pomegranate Juices During Refrigerated Storage - Faten Boussaa; Faten Zaouay; Messaoud Mars (Indonesian Association of Food Technologists, 2021)
Physicochemical and microbiological properties changes of new beverages combining sour (‘Garoussi 2’, ‘Mezzi 1’, ‘Mezzi 2’) and sweet (‘Gabsi’, ‘Tounsi’) pomegranate juices with different proportions (10% and 20% of sour juices) were studied over a 14 days refrigerated storage. The sour juices have proved to be very rich in total soluble solids, total anthocyanin and total phenolic contents. However, these juices are not appreciated by panellists because of high acidity content. The juice blends were characterized by an attractive red colour, acceptable acidity, higher total soluble solids content, higher total phenol and anthocyanin contents compared to sweet juices. The juice blending was found to be very effective in reducing the browning and improving the appearance of beverages during storage. High microbial loads of juice samples stored up to 14 days indicate their poor microbiological quality. The beverage based on Gabsi and Garoussi 2 (10 % and 20 % proportions) presented better nutritional and microbiological stability during storage leading to their high consumer acceptance. It was concluded that conservation of juice samples should not exceed 7 days in order to have healthy value-added beverages.